Pengaruh Pelaksanaan Tata Tertib dan Keteladanan Guru terhadap Kedisiplinan Belajar Siswa pada Pembelajaran Pendidikan Agama Islam - Mujahidin Muda; Mas'ud Zein; Nurhasanah Bakhtiar; Muspika Hendri (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
This study aims to see whether there is an effect of the implementation of discipline and exemplary teachers on student learning discipline in Islamic Religious Education learning at SMP Negeri Lima Puluh District, Pekanbaru City. This research is based on the problem of low student learning discipline. The research method uses quantitative research using correlational analysis techniques. The population in this study were all students of SMPN in Lima Puluh District, Pekanbaru City, totaling 2,459 people. The sample in this study was taken with a proportionate random sampling technique with the Slovin formula, namely 346 people. Data collection was done by using a questionnaire technique, the data collected was analyzed using multiple regression analysis, namely Y = a + b1X1 + b2 X2. The results of this study indicate the value of R2 (coefficient of determination) or R Square of 0.472 or 47.2%. This value can be interpreted that the change in the discipline of student learning by the change in the value of the independent variable in the implementation of discipline and teacher's role model is 47.2%, while 52.8% is determined by changes in other factors. The tcount value for the discipline implementation variable is 14,832 with sig. 0.000 is smaller than 0.05, this means that there is an effect of discipline implementation on student learning discipline and tcount for teacher exemplary variables is 2.234 with sig. 0.026 is smaller than 0.05, this means that there is an effect of teacher modeling on student learning discipline. It can be concluded that there is an influence between the implementation of discipline and teacher exemplary on student learning discipline in Islamic Religious Education learning at SMP Negeri Lima Puluh District, Pekanbaru City.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//